Systems change: A guide to what it is and how to do it (NPC, 2015)
Systems change has been attracting the attention of those in the socia l sector who want to deal with the root causes of problems, but, despi te the buzz, much of what is written is abstract in tone. With the sup port of LankellyChase Foundation we have produced this guide to plug a gap in the systems change literature—providing accessible material an d recommendations for action. Systems change has been attracting the a ttention of a range of progressive charities, funders and practitioner s who are interested in dealing with the root causes of social problem s. But while there is a buzz about a subject relatively new to the soc ial sector, it is easy to feel frustrated by the literature—much of wh at is written is abstract in tone and there are few examples of succes s. We have produced this paper to address this problem and offer acces sible material and recommendations for action. This systems change gui de: Clarifies what is meant by systems and systems change Describes th e main perspectives on systems change Outlines good practice for syste ms change Identifies what is and is not agreed upon by experts in the field Provides recommendations for charities, funders and the public s ector on how to act systemically. We hope this presents a manageable i ntroduction to the systems change field, especially for those new to i t, and also guides those interested in acting systemically to improve the lives of people in need. Our conclusion is that although it may no t be as novel as some claim, there is a good deal of value in a system s change approach and it offers a welcome reminder of what effective a ction looks like when it comes to the pursuit of social change.